2010
DOI: 10.1075/eww.31.1.02chi
|View full text |Cite
|
Sign up to set email alerts
|

Nigerian English in informal email messages

Abstract: This study applies a sociolinguistic and discourse-analytical methodology to the study of features and manifestations of Nigerian English in computer-mediated communication, particularly informal emails. The data comprise 133 email samples consisting of messages received or sent within a seven-year period, i.e. between 2002 and 2009, from typical Nigerian environments, as well as by the youth, adults and the elderly. Analyses reveal that the rise of new media technologies and digital communication has provided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 10 publications
0
8
0
2
Order By: Relevance
“…In some cases, these official titles may be combined with first person pronouns such as My HOD. Such examples have been noted in Chiluwa (2010) where he cites examples such as My Prof in email messages. On some occasions, a term like HOD may be used in order to get a request done as an interviewee notes:…”
Section: Official and Occupational Titlesmentioning
confidence: 88%
See 1 more Smart Citation
“…In some cases, these official titles may be combined with first person pronouns such as My HOD. Such examples have been noted in Chiluwa (2010) where he cites examples such as My Prof in email messages. On some occasions, a term like HOD may be used in order to get a request done as an interviewee notes:…”
Section: Official and Occupational Titlesmentioning
confidence: 88%
“…As Chiluwa (2010) observes, Nigerians have a title-conscious tradition, which transcends the academic setting. Moreover, the clipped terms, prof and doc are used to indicate familiarity between the addresser and addressee (see also Chiluwa [2010] for the use of prof as salutations in Nigerian informal email messages). These clipped items are also usually used when the interactants are close as they occur in banter amongst friends.…”
Section: Academic Titlesmentioning
confidence: 99%
“…Mientras que en los países occidentales la repercusión de los estudios lingüísticos sobre la comunicación en Internet es manifiesta, en África podemos destacar la labor llevada a cabo por algunos autores nigerianos como Chiluwa (2010aChiluwa ( , 2010b, quien ha publicado y editado varias obras con repercusión internacional que tratan de la creación de la identidad nigeriana en los correos electrónicos en inglés de Nigeria o sobre la pragmática de las llamadas cartas nigerianas.…”
Section: La Comunicación Electrónica En áFrica Y Camerúnunclassified
“…A pesar del gran alcance académico de estas publicaciones, su área de influencia se limita, en gran medida, al mundo occidental, mientras que en otros continentes como el africano, todavía no han alcanzado su máximo desarrollo. En África, en efecto, el estudio de la repercusión de Internet en la vida diaria de los ciudadanos y en el ámbito académico está en un estadio incipiente, exceptuando algunos casos como el de Chiluwa (2010aChiluwa ( , 2010b, aunque poco a poco va ganando espacio y despertando el interés de la comunidad universitaria. En Camerún, la ausencia de investigaciones sobre la comunicación electrónica es aún si cabe más patente por la escasa penetración de Internet que ha obligado a que nuestro estudio se centre en un género específico de la comunicación electrónica: las cartas de bienvenida a las instituciones de educación superior.…”
Section: Introductionunclassified
“…Adverts, questions, rendezvous immediate and ongoing, rendezvous near future, events, instructions, reminders, jokes, sign on , sign off, gossip, dates, information-personal, informationcommercial, information-operational In Nigeria, some studies (e.g. Awonusi, 2004;Chiluwa, 2010) have shown that the linguistic forms and practices of the English of SMS text messages have become so popular among the youth (16-25) and young adults (25-45).…”
Section: 1sms Text Messages As Discoursementioning
confidence: 99%